An Enhanced Approach for Wi-Fi Security and Authentication Protocols: A Systematic Approach towards WEP, WPA, WPA2, and WPA3 - Faiza Afzal,; Ahmad Uzair,; M. Aetsam Javed,; Syed Asad Ali Naqvi, (Spectrum of Engineering Sciences, 2024)
The size of wireless networks and the number of wireless devices are growing daily. A crucial part of wireless security involves preventing unauthorized access by using wireless security protocols to protect the data in wireless networks. The article examines security threats facing wireless networks and the effectiveness of security protocols deployed to combat these threats. The thesis will base its study on Wireless Local Area Networks (WLAN) as defined by IEEE standards 802.11a/b/g/n. Features of each WLAN Security protocol, from WEP, WPA and IEEE 802.11i will be analyzed and the effectiveness of each protocol in ensuring data integrity, data confidentiality, and network availability will be presented. The evolution of Wi-Fi security protocols has paralleled the growing demand for secure wireless communication in an interconnected world. Starting with the flawed Wired Equivalent Privacy (WEP), the journey toward robust security has seen the development of WPA, WPA2, and WPA3. Each protocol aimed to address the vulnerabilities of its predecessor, adopting more sophisticated encryption techniques and authentication mechanisms. This paper provides a comprehensive analysis of these protocols, highlighting their technical advancements, weaknesses, and real-world applications. Through systematic review methodologies and real-time examples, the study underscores the critical need for continuous innovation to combat emerging cyber threats in an era of rapid technological advancement. In a network where frequent handovers of a client device are required from one Access point to another; the large latencies may lead to poor Quality of Service (QoS) or even interruption of real-time and interactive network services such as Voice over Internet Protocol (VOIP). Keywords: Wi-Fi security, wireless protocols, WEP, WPA, WPA2, WPA3, cybersecurity, encryption, authentication, real-world examples.